Protection from cisplatin-induced hearing loss with lentiviral vector-mediated ectopic expression of the anti-apoptotic protein BCL-XL - Larissa Nassauer; Hinrich Staecker; Peixin Huang; Bryan Renslo; Madeleine Goblet; Jennifer Harre; Athanasia Warnecke; Juliane W. Schott; Michael Morgan; Melanie Galla; Axel Schambach (Elsevier, 2024)
Cisplatin is a highly effective chemotherapeutic agent, but it can cause sensorineural hearing loss (SNHL) in patients. Cisplatin-induced ototoxicity is closely related to the accumulation of reactive oxygen species (ROS) and subsequent death of hair cells (HCs) and spiral ganglion neurons (SGNs). Despite various strategies to combat ototoxicity, only one therapeutic agent has thus far been clinically approved. Therefore, we have developed a gene therapy concept to protect cochlear cells from cisplatin-induced toxicity. Self-inactivating lentiviral (LV) vectors were used to ectopically express various antioxidant enzymes or anti-apoptotic proteins to enhance the cellular ROS scavenging or prevent apoptosis in affected cell types. In direct comparison, anti-apoptotic proteins mediated a stronger reduction in cytotoxicity than antioxidant enzymes. Importantly, overexpression of the most promising candidate, Bcl-xl, achieved an up to 2.5-fold reduction in cisplatin-induced cytotoxicity in HEI-OC1 cells, phoenix auditory neurons, and primary SGN cultures. BCL-XL protected against cisplatin-mediated tissue destruction in cochlear explants. Strikingly, in vivo application of the LV BCL-XL vector improved hearing and increased HC survival in cisplatin-treated mice. In conclusion, we have established a preclinical gene therapy approach to protect mice from cisplatin-induced ototoxicity that has the potential to be translated to clinical use in cancer patients.